Clause-sensitivity of inflectional morphology in L2 English / Yuji Shuhama - Shuhama, Yuji (Akademi Pengajian Bahasa, 2021)
Interface Hypothesis (Sorace and Filiaci 2006) developed in line with the Minimalist theory of grammar (Chomsky 1995 et seq.) supports the view of L2 acquisition that syntactic properties are acquired early while the acquisition of interface properties is delayed. One of the latter phenomena is inflectional morphology on English verbs, which involves subject-verb- and inter-clausal agreement at the syntaxmorphology interface. Previous studies (e.g., Nakayama and Yoshimura 2015) have revealed that for learners of L2 English, acquiring third person singular -s is harder than regular past -ed due to the absence of meaningless morphemes in L1. However, one question has been disregarded: Where in a clause are these morphemes inserted more successfully? The following sample shows a contrast between two clauses: *When you go to NY from Tokyo, it took almost 30 days by ship. Given that subordinate clauses are grammatically more restricted than main clauses (Aelbrecht et al. 2012), this study examines the clause-sensitivity of L2 inflectional morphology. 44 Japanese university students learning English as L2 were asked to complete a grammaticality judgment test and write an essay about a specified topic. The learners’ inflection pattern was surveyed through the test scores and text analysis of over 400 sentences in the essays. Results show that the correct judgment rate is significantly higher in finite clauses than non-finite clauses, but in writing, inaccurate verb inflection is found frequently regardless of clause types. These findings support Interface Hypothesis and further imply the importance of clauses as meaningful units in L2 grammar instructions.